Implementation of Law No. 5 of 1960 in the Acquisition of Regionally Owned Land from the Perspective of the Due Process of Law Principle: An Empirical Study in Laju Village, Langgudu District, Bima Regency - Wisdarjon Wisdarjon; Ihlas Ihlas; Hj. Adnan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to analyze the implementation of Law Number 5 of 1960 concerning the Basic Agrarian Principles in the acquisition of regional government-owned land and to examine its conformity with the principle of due process of law in Laju Village, Langgudu District, Bima Regency. The acquisition of government-owned land must be carried out in accordance with the applicable laws and regulations while ensuring the protection of community rights through procedures that are fair, transparent, and accountable. This research employed an empirical legal approach using both statutory and socio-legal approaches. Primary data were obtained through interviews with the Head of Laju Village, the Head of Langgudu District, officials of the National Land Agency (BPN) of Bima Regency, and affected community members. Secondary data were collected through a literature review of laws and regulations, books, scientific journals, and other relevant documents. All data were analyzed using a descriptive qualitative method. The findings indicate that the implementation of land acquisition in Laju Village has not been carried out optimally. Several obstacles were identified, including weak inter-agency coordination, a lack of transparency, limited public participation, and inadequate land administration. From the perspective of due process of law, the implementation has not fully fulfilled the principles of legality, legal certainty, transparency, public participation, and the protection of community rights. Therefore, strengthening supervisory mechanisms, improving inter-agency coordination, and implementing more transparent, accountable, and rights-oriented procedures are essential to ensuring legal certainty in every process of regional government-owned land acquisition.